Measurement of the production of neighbouring jets in lead?lead collisions at √sNN=2.76TeV with the ATLAS detector - Aad, G. (2015)
This Letter presents measurements of correlated production of nearby jets in Pb+Pb collisions at √sNN = 2.76 TeV using the ATLAS detector at the Large Hadron Collider. The measurement was performed using 0.14 nb−1 of data recorded in 2011. The production of correlated jet pairs was quantified using the rate, R∆R, of “neighbouring” jets that accompany “test” jets within a given range of angular distance, ∆R, in the pseudorapidity–azimuthal angle plane. The jets were measured in the ATLAS calorimeter and were reconstructed using the anti-kt algorithm with radius parameters d = 0.2, 0.3, and 0.4. R∆R was measured in different Pb+Pb collision centrality bins, characterized by the total transverse energy measured in the forward calorimeters. A centrality dependence of R∆R is observed for all three jet radii with R∆R found to be lower in central collisions than in peripheral collisions. The ratios formed by the R∆R values in different centrality bins and the values in the 40–80% centrality bin are presented.